Nonlinear learning pedagogy: Does it have an impact on physical education in elementary schools? - Pasca Tri Kaloka; Soni Nopembri; Yudanto Yudanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2023)
Abstract. Nonlinear pedagogy has the potential to be an effective strategy for teaching and studying physical education in elementary school a way that allows students to develop their skills. This study aims to determine whether there is an effect of physical education teacher readiness in implementing nonlinear pedagogy learning in Indonesia, Malaysia, and the Philippines. This Study used an experimental method with one group pre-test-post-test design. The research participants were physical education teachers in elementary schools in Indonesia, Malaysia, and the Philippines (n = 90). 40 question online survey with a validity level of 0.74 and a reliability level of 0.80 is used to assess teacher preparedness for implementing nonlinear learning. With the aid of a literature review, secondary data was gathered. The paired sample t-test results revealed that 0.05 > 0.000, indicating that the data variance was the same. The significance result indicates that 0.000 < 0.05 (confidence interval = 99%) when looking at the assumed equal variances, which means that H0 is rejected. According to the data, there are 25 teachers or 27,8% who are ready to carry out nonlinear pedagogy learning, 42 teachers or 46,7% are not ready, and 23 teachers or 25,5% are unprepared. Nonlinear pedagogy learning has an effect on PE teachers' readiness in the three countries. The intended effect is to demonstrate that PE teachers are not ready to use nonlinear pedagogy in their lessons. The recommendation from the finding is that teachers need training in nonlinear pedagogy and adequate support to succeed in nonlinear pedagogy learning.